Immunohistochemical Comparison of the Expression of CD34 and CD105 in Odontogenic Keratocyst and Dentigerous Cyst - Jamshidi, Shokoofeh (J Dent (Shiraz), 2017)
STATEMENT OF THE PROBLEM: Odontogenic keratocyst (OKC) is a developmental odontogenic cyst with specific histopathological features, high recurrence rate, and aggressive clinical behavior. Angiogenesis might be considered as an important factor for the growth, expansion, and distribution of this lesion. PURPOSE: The aim of the present study was to determine the mean vascular densities (MVD) of OKCs and dentigerous cysts to evaluate their relationship with the biologic behavior of these lesions. MATERIALS AND METHOD: In this cross-sectional analytical study, angiogenesis was assessed in OKC and dentigerous cyst by measuring the MVD. Immunohistochemistry was carried out using CD34 and CD105. The results were analyzed with independent samples t-test. The data were analyzed, setting p value at 0.05. RESULTS: The MVDs with the use of CD34 and CD105 markers were significantly higher in OKC compared to dentigerous cyst (p< 0.05). In addition, MVDs obtained by CD105 in dentigerous cysts and OKC were significantly less than those based on CD34 (p< 0.05). CONCLUSION: Based on the results of the present study, it can be suggested that angiogenesis might be one of the possible mechanisms involved in higher aggressive biologic behavior and greater recurrence rate of OKC compared to dentigerous cysts.